2022
DOI: 10.1098/rsif.2022.0440
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian modelling framework to quantify multiple sources of spatial variation for disease mapping

Abstract: Spatial connectivity is an important consideration when modelling infectious disease data across a geographical region. Connectivity can arise for many reasons, including shared characteristics between regions and human or vector movement. Bayesian hierarchical models include structured random effects to account for spatial connectivity. However, conventional approaches require the spatial structure to be fully defined prior to model fitting. By applying penalized smoothing splines to coordinates, we create tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Mathematical modeling has been extensively used in many different fields of study including medicine, physics, economics, and so on [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Medical research issues, especially high-level medical research achievements, often rely on the establishment of reasonable medical mathematical models [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, Tripathi et al [7] provided several examples of designing various mathematical models that can help us better comprehend dynamics at the single-cell and population levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical modeling has been extensively used in many different fields of study including medicine, physics, economics, and so on [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Medical research issues, especially high-level medical research achievements, often rely on the establishment of reasonable medical mathematical models [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, Tripathi et al [7] provided several examples of designing various mathematical models that can help us better comprehend dynamics at the single-cell and population levels.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [8] proposed a dynamic Boolean network to categorize gene regulation between two non-coding RNAs (ncRNAs) in gastric cancer, which opens up a new avenue for gastric cancer treatment in response to DNA damage caused by these ncRNAs. Lee et al [9] utilized Bayesian inference and simulation to determine the relative contribution of each spatial structure and used it to generate hypotheses concerning the drivers of disease. The results demonstrated that Bayesian hierarchical models performed at least as well as existing modeling frameworks while permitting extensions in the future and multiple sources of spatial connectedness.…”
Section: Introductionmentioning
confidence: 99%
“…The model includes the fixed effects of the covariates as well as spatial and temporal random effects and the spatiotemporal interaction [7]. The principal focuses of disease-mapping models are disease map reconstruction, model evaluation, and the quantification of multiple risk factors for spatiotemporal variation in disease risk [8,9].…”
Section: Introductionmentioning
confidence: 99%